Effect of bainitic transformation on the microstructure and wear resistance of pearlitic rail steel. Issue 9 (20th October 2020) - Tressia, Gustavo; Alves, Luis H.D.; Sinatora, Amilton; Goldenstein, Helio; Masoumi, Mohammad
Abstract : Purpose: The purpose of this study is to develop a lower bainite structure consists of a dispersion of fine carbide inside plates of bainitic ferrite from chemical composition unmodified conventional pearlitic steel under bainitic transformation and to investigate its effect on tensile properties and wear resistance. Design/methodology/approach: A commercial hypereutectoid pearlitic rail steel was subjected to three different bainitic transformation treatments followed by tempering to develop a desirable microstructure with a DIL805 BÄHR dilatometer. A comprehensive microstructural study was performed by scanning electron microscopy and energy dispersive x-ray spectroscopy. Finally, the mechanical properties and wear resistance were evaluated by tensile, microhardness, and pin-on-disc tests. Findings: The results showed that the best combination of mechanical properties and sliding wear resistance was obtained in the sample subjected to bainitic transformation at 300°C for 600 s followed by tempering at 400°C for 300 s. This sample, which contained a bainitic ferrite structure, exhibited approximately 20% higher hardness and approximately 53% less mass loss than the as-received pearlitic sample due to the mechanically induced transformation in the contact surface. Originality/value: Although pearlitic steel is widely used in the construction of railways, recent studies have revealed that bainitic transformation at the same rail steels exhibited higher wear resistance and fatigue strengths than conventional pearlitic rail at the same hardness values. Such a bainitic microstructure can improve the mechanical properties and wear resistance, which is a great interest in the railway industry. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-07-2019-0282/